The Effect of Human Resources Competence, Information Technology Utilization, and Data Reconciliation on The Quality of Financial Reports with Organizational Commitment as a Moderating Variable - Ni Kadek Muda Wardani; I Putu Gede Diatmika; Desak Nyoman Sri Werastuti (International Journal of Social Science and Business, 2023)
The quality of BMKG's financial reports needs to be improved in the context of bureaucratic reform and efforts to achieve transparency and accountability in government financial reporting. This research aims to analyze the influence of human resource competency, utilization of information technology, and data reconciliation with organizational commitment as a moderating variable on the quality of BMKG's financial reports. Non-probability sampling with purposive sampling was used to select the sample, resulting in 254 respondents participating in this study. The data used were primary and secondary data. The data analysis method employed was Partial Least Squares Structural Equation Modelling (PLS SEM) using the Smart PLS program. The results of this research indicate that human resource competency, utilization of information technology, and data reconciliation have a significant positive effect on the quality of financial reports. Organizational commitment as a moderating variable can strengthen the influence of human resource competency on the quality of financial reports, but it cannot enhance the influence of information technology utilization and data reconciliation on the quality of financial reports. The implication of this research highlights the importance of developing human resource competency and implementing appropriate information technology in the preparation of high-quality financial reports.